2018
DOI: 10.1038/s41579-018-0064-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of viral oncogenesis in humans

Abstract: Viral infection is a major contributor to the global cancer burden. Recent advances have revealed that seven known oncogenic viruses promote tumorigenesis through shared host cell targets and pathways. A comprehensive understanding of the principles of viral oncogenesis may enable the identification of unknown infectious aetiologies of cancer and the development of therapeutic or preventive strategies for virus-associated cancers. In this Review, we discuss the molecular mechanisms of viral oncogenesis in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
224
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(229 citation statements)
references
References 152 publications
0
224
0
5
Order By: Relevance
“…miRNAs are a class of short (18–25 nucleotides) non-coding small RNAs, which are widely found in eukaryotes. The discovery of miRNAs ranks first among the world’s top 10 technological breakthroughs in Science in 2002. miRNAs are involved in the regulation of various biological processes including autophagy ( Hargarten and Williamson, 2018 ), tumors ( Krump and You, 2018 ), allergic diseases ( Tost, 2018 ), and T-cell immunity ( Giri et al, 2019 ) for mediating gene silencing. Numerous investigations have shown that miRNAs play a vital role in PNI and peripheral nerve repair; for instance, the expression of miRNAs in dorsal root ganglia (DRG) tissues after sciatic nerve injury in rats was significantly changed ( Li et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are a class of short (18–25 nucleotides) non-coding small RNAs, which are widely found in eukaryotes. The discovery of miRNAs ranks first among the world’s top 10 technological breakthroughs in Science in 2002. miRNAs are involved in the regulation of various biological processes including autophagy ( Hargarten and Williamson, 2018 ), tumors ( Krump and You, 2018 ), allergic diseases ( Tost, 2018 ), and T-cell immunity ( Giri et al, 2019 ) for mediating gene silencing. Numerous investigations have shown that miRNAs play a vital role in PNI and peripheral nerve repair; for instance, the expression of miRNAs in dorsal root ganglia (DRG) tissues after sciatic nerve injury in rats was significantly changed ( Li et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although oncogenic viruses converge in common features from a broad perspective, divergent genomes, oncogenic factors, cellular tropism, and disease prevalence distinguish each of those infectious agents ( 12 , 13 ). Nonetheless, polyploidy appears to be a crossroad and a biological equivalency trait shared among oncoviruses, where the latter could be regarded as an initiating engine that fuels phenotypic diversity.…”
Section: Introductionmentioning
confidence: 99%
“…The classification of gastric carcinomas of diffuse type as adenocarcinomas, despite no glandular growth pattern, is partly based upon periodic acid-Schiff (PAS) positivity regarded as a marker of mucin. However, when applying much more sensitive and specific methods like immunohistochemistry and in situ hybridization, we could not find any mucin in the PAS positive cancer cells [35,38]. Thus, the ECL cell, a well differentiated cell, can divide, and it is possible to follow the tumorigenic process via hyperplasia to rather benign NETs, highly malignant NECs, and further to some carcinomas hitherto classified as adenocarcinomas.…”
Section: Gastric Cancermentioning
confidence: 83%